SOME SCIENTIFIC-THEORETICAL APPROACHES AND CONCEPTS CONCERNING THE VALUES - Khodievna, Ruzieva Ruhsora (The journal of contemporary issues in business and government, 2022)
Values, both from the perspective of functional features and from the perspective of sub stantional essence, are the overarching phenomena that are important for humans, their lives, and activities. Therefore, some researchers and authors look for values from everywhere, even from myths, fairytales, and folklore. We think that approaching the problem in such a wide scope leads to the widening of the topic and sphere of the research to an unproductive degree. If the study of values are the objects of the axiology, then its research sphere must also be limited.